Environmental and Genetic Stressors and the Unfolded Protein Response in Exocrine Pancreatic Function – A Hypothesis - Pandol, Stephen J.; Gorelick, Fred; Lugea, Aurelia (Frontiers in Physiology, 2011)
The exocrine pancreas has the greatest synthetic capacity of any mammalian organ and as such is challenged with synthesis, processing and transporting a large load of digestive enzymes. Here we discuss how both mutations in the digestive enzymes and environmental factors impacting the pancreas such as alcohol abuse, smoking, metabolic disorders and drugs can cause Endoplasmic Reticulum (ER) stress. We describe that in normal pancreas the ER stress resulting from alcohol abuse leads to an adaptive Unfolded Protein Response (UPR) allowing for maintenance of protein synthesis, processing and transport. However, when key pathways necessary for the adaptive UPR are altered, the exocrine cell of the pancreas is unable to maintain these processes and cellular pathology results. These findings provide better insights to explain why some individuals with alcohol abuse disorders develop organ injury and disease while most do not. Further, the approach and models described here can be used to determine the relative roles of ER stress and the UPR for other etiologies of pancreatic diseases.